An Inventive and Innovative Alternate for Legacy Chain Pulling System through Internet of Things - Budaraju Sri Datta; Rama Ganapathy; Sini Raj P; Shriram K Vasudevan; Abhishek SN (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Indian Railways made a move in replacing the chain pulling system with the new mobile based communication system where the loco pilot’s mobile phone number shall be shared with all the passengers through a message. Despite the efforts taken to remove the chains from the train, there is a great probability of misuse through the mobile phone number provided. We aim to build a more efficient and secure solution based on the Internet of Things, which is a buzz word in the market. Our proposed system provides an alarm fixed at specific locations in the compartments of a train. In case of emergency, the passenger has to press the alarms’ button, which captures the scene using a built-in digital camera. The system also alarms the Loco-Pilot, Travelling Ticket Examiner, as well as the compartment so as to provide immediate possible help through the fellow co-passengers. The pilot slows down the train to an optimum speed whilst the travelling ticket examiner checks and confirms the pilot whether he has to stop the train. The entire system can be controlled through an authenticated mobile application provided to the ticket examiner. The pictures captured by the camera and other crucial details are uploaded to a cloud-based real-time database. Thus, saving time and taxpayers’ money as well as helping the railways to perform analytics and come up with feasible solutions to the problems of the passengers. The system has the potential to deal with the most prevailing cargo theft like that of coal, by alerting the staff without having to stop the train, making the convicts’ escapes impossible. This also definitely avoids the improper pulling of chains and thereby not causing any hassle to the passengers as well as diminishes the economic loss to the government by reducing the time delay.